The battle for broadband [Internet protocol television]. - Cherry, S. (IEEE spectrum)
This paper discusses the role of Swiss telephone carriers and cable providers in the highly competitive telecommunications market. A key technological development is the software platform called Internet Protocol television (IPTV). At the forefront is the Bern-based Swiss phone company, Swisscom AG. Swisscom has conducted tests to determine its ability to deliver video and win customers from cable using IPTV technology. Results of the tests will significantly alter the future direction of the telecommunication industry, and that of a big chunk of the entertainment world as well.